2018
DOI: 10.1111/phn.12516
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Arab Nursing Students' Attitudes toward Climate Change and Environmental Sustainability and their Inclusion in Nursing Curricula

Abstract: The inclusion of climate change and environmental sustainability in nursing curricula in the Arab region was emphasized by the findings. Including environmental sustainability practices in nursing education will help student nurses develop critical thinking and skills in the adaptive delivery of health care, especially when resources are scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 25 publications
2
34
0
1
Order By: Relevance
“…In two related surveys, a majority of national and international American Thoracic Society respondent members indicated that climate change is happening, already affecting patients’ health [ 13 , 14 ]. Five surveys targeted nursing and medical education curricula, which indicated perceived needs to include climate change and environmental sustainability topics in their programs [ 15 , 16 , 17 , 18 , 19 ]. One, limited, survey among patients visiting a general practice in Israel [ 20 ] and a larger U.S. population survey [ 21 ] indicated that, although aware that global warming may harm health, patients and population need, and may expect, more complete and specific information about health in relation with climate and environmental changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In two related surveys, a majority of national and international American Thoracic Society respondent members indicated that climate change is happening, already affecting patients’ health [ 13 , 14 ]. Five surveys targeted nursing and medical education curricula, which indicated perceived needs to include climate change and environmental sustainability topics in their programs [ 15 , 16 , 17 , 18 , 19 ]. One, limited, survey among patients visiting a general practice in Israel [ 20 ] and a larger U.S. population survey [ 21 ] indicated that, although aware that global warming may harm health, patients and population need, and may expect, more complete and specific information about health in relation with climate and environmental changes.…”
Section: Resultsmentioning
confidence: 99%
“…The typical article was a perspective, commentary, or other special article aimed at informing and alerting readers about the links between climate and environment change and human health. to include climate change and environmental sustainability topics in their programs [15][16][17][18][19]. One, limited, survey among patients visiting a general practice in Israel [20] and a larger U.S. population survey [21] indicated that, although aware that global warming may harm health, patients and population need, and may expect, more complete and specific information about health in relation with climate and environmental changes.…”
Section: Global Analysismentioning
confidence: 99%
“…Los líderes de enfermería, llegaron a un consenso de que lo más importante es fortalecer el currículo de enfermería, teniendo en cuenta los cambios y la sostenibilidad del entorno social, e involucrando aspectos como la promoción de la salud ambiental, la justicia social, la igualdad económica que permitan vivir en un mundo adecuado 11 . Ante ello, existe un vínculo entre sostenibilidad, cambio climático y salud que hace imperativo que se examinen las nociones de sostenibilidad y cambio climático en la educación de enfermería 12 .…”
Section: Discussionunclassified
“…However, barriers to doing so included a resistance to change amongst clinical staff, in some cases related to negative staff attitudes (Aronsson et al, 2020). To learn about climate change and sustainability, Cruz et al (2018) suggest that nursing students need positive attitudes towards these concepts, including a sense of responsibility, a willingness to change and a confidence in the future (Lopez-Medina et al, 2019). To prepare future nurses for their role, nursing educators have a duty to ensure that nursing programmes reflect changing needs, developments, priorities and expectations in health and health care.…”
mentioning
confidence: 99%
“…The implementation of sustainability will contribute to a development that maintains an environment that does not harm current and future generation's opportunities for good health. Anåker & Elf (2014, p.387) Cruz et al (2018) suggest that increased awareness about climate change and sustainability can motivate nurses to adopt sustainable practices; this includes waste management in the clinical environment (Nichols & Mukonoweshuro, 2017). Aronsson et al (2020) found that educational sessions that focused on the relevance of climate change and sustainability to health and health care in undergraduate courses could lead nursing students to challenge unsustainable clinical practice.…”
mentioning
confidence: 99%